Investigating the molecular mechanisms of resveratrol in treating diabetic foot ulcers: a comprehensive analysis of network pharmacology and experiment validation - Sima, Chao; Wang, Zhe; Wang, Sisi; Wang, Haiyang; Sun, Zhonghua; Wang, Haoguo; Liang, Daning; Li, Jianchi; Zhang, Zhenning (Frontiers in Molecular Biosciences, 2025)
BackgroundDiabetic foot ulcers (DFU) are one of the most common and severe complications of diabetes, closely associated with high amputation rates and mortality, and the clinical treatment research is still limited. Previous studies have demonstrated that resveratrol exerts positive effects in wound healing. Therefore, it is necessary to investigate its molecular mechanisms in treating DFU to improve clinical management of this condition.MethodsThis study obtained DFU-related omics data from the GEO database and predicted targets for Resveratrol from TCMSP, PharmMapper, and Swiss Target Prediction. Differential analysis, weighted gene co-expression network analysis (WGCNA), and machine learning were used to jointly identify hub Resveratrol/DFU genes (RDGs). SsGSEA analysis was employed to investigate the relationship between RDGs and the DFU immune microenvironment. Single-cell RNA-seq was employed to investigate cellular heterogeneity of RDGs expression. Molecular docking studies examined interactions between RDGs and resveratrol. Finally, immunohistochemistry validated RDGs expression.ResultsFirst, bioinformatics analyses and machine learning algorithms identified Cytidine deaminase (CDA) and Ornithine Decarboxylase 1 (ODC1) as RDGs. Second, ROC curves demonstrated RDGs’ strong diagnostic performance for DFU. The ssGSEA algorithm revealed that RDGs partially mediate the immune microenvironment of DFU. Subsequently, scRNA-seq results demonstrated cellular heterogeneity of RDGs expression, which mediates alterations in the pathological microenvironment of DFU and consequently influences its progression. Subsequently, molecular docking revealed strong binding affinity between resveratrol and RDGs, suggesting resveratrol may exert therapeutic effects on DFU by regulating RDG activity through binding. Finally, immunohistochemistry further validated RDG expression, providing strong evidence for RDGs as novel therapeutic targets for DFU.ConclusionOverall, this study identified RDGs as a key therapeutic target for resveratrol acting on DFU through a series of bioinformatics analyses and machine learning algorithms. Which not only fills the gap in the molecular mechanism of resveratrol treatment for DFU but also provides a novel therapeutic target for DFU.